2023
DOI: 10.1109/access.2023.3285115
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Alzheimer’s Disease Using Convolutional Neural Network With Select Slices by Landmark on Hippocampus in MRI Images

Abstract: Alzheimer's disease (AD) is a major public health priority. Hippocampus is one of the most affected areas of the brain and is easily accessible as a biomarker using MRI images in machine learning for diagnosing AD. In machine learning, using entire MRI image slices showed lower accuracy for AD classification. We present the select slices method by landmarks on the hippocampus region in MRI images. This study aims to see which views of MRI images have higher accuracy for AD classification. Then, to get the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The annotation work was manually outlined by three medical experts, and then segmented and annotated by five computer annotators using Lableme. After the dataset was generated, it was finally reviewed by three medical experts to obtain the final dataset ( Pusparani et al, 2023 ). Another problem is the shape is irregular and the contrast with its surrounding tissue is not obvious.…”
Section: Methodsmentioning
confidence: 99%
“…The annotation work was manually outlined by three medical experts, and then segmented and annotated by five computer annotators using Lableme. After the dataset was generated, it was finally reviewed by three medical experts to obtain the final dataset ( Pusparani et al, 2023 ). Another problem is the shape is irregular and the contrast with its surrounding tissue is not obvious.…”
Section: Methodsmentioning
confidence: 99%
“…[ 15 ] developed a robust low-cost neural network classification system for AD and Mild Cognitive Impairment (MCI) against NC using a CNN with input images based on diffusion maps and gray-matter volumes, achieving competitive results of 93.5% for AD/NC classification. In another study relating raw MRI data [ 16 ], the authors employed ResNet-50 and LeNet on AD classification based on MRI slices in three views and categories. The study demonstrated that the selecting slices performed better than using entire slices in MRI images for AD classification and the coronal view showed higher accuracy.…”
Section: Introductionmentioning
confidence: 99%